+0  
 
0
990
1
avatar+587 

The recursive rule for a sequence is shown.

an=an−1+6

a1=39

 

What is the explicit rule for this sequence?

 

  • an=33n−6
  • an=6n−33
  • an=6n+33
  • an=33n+6
 Feb 7, 2018
 #1
avatar+111329 
+1

an = an-1 + 6,  a1  = 39

 

Note that the terms are

 

39, 45, 51, 55.......

 

So....we can write

 

6(1) + 33, 6(2) + 33, 6(3) + 33 , 6(4) + 33

 

So...the explicit rule is

 

an  = 6n + 33

 

 

 

cool cool cool

 Feb 7, 2018

24 Online Users

avatar
avatar
avatar
avatar
avatar
avatar